Agonist and antagonist switch DNA motifs recognized by human androgen receptor in prostate cancer. (22nd December 2014) - Chen, Zhong; Lan, Xun; Thomas‐Ahner, Jennifer M; Wu, Dayong; Liu, Xiangtao; Ye, Zhenqing; Wang, Liguo; Sunkel, Benjamin; Grenade, Cassandra; Chen, Junsheng; Zynger, Debra L; Yan, Pearlly S; et al.
Abstract Human transcription factors recognize specific DNA sequence motifs to regulate transcription. It is unknown whether a single transcription factor is able to bind to distinctly different motifs on chromatin, and if so, what determines the usage of specific motifs. By using a motif‐resolution chromatin immunoprecipitation‐exonuclease (ChIP‐exo) approach, we find that agonist‐liganded human androgen receptor (AR) and antagonist‐liganded AR bind to two distinctly different motifs, leading to distinct transcriptional outcomes in prostate cancer cells. Further analysis on clinical prostate tissues reveals that the binding of AR to these two distinct motifs is involved in prostate carcinogenesis. Together, these results suggest that unique ligands may switch DNA motifs recognized by ligand‐dependent transcription factors in vivo. Our findings also provide a broad mechanistic foundation for understanding ligand‐specific induction of gene expression profiles.